Erenumab Impact on Sleep Assessed With Questionnaires and Home-Polysomnography in Patients With Migraine: The ERESON Study - Pellitteri, Gaia; Pez, Sara; Nilo, Annacarmen; Surcinelli, Andrea; Gigli, Gian Luigi; Lettieri, Christian; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Introduction Migraine and sleep share a complex and unclear relationship. Poor sleep may trigger migraine attacks; migraine, in turn, is frequently associated with sleep disorders. Few previous studies used questionnaires to assess sleep changes in patients who were treated with migraine-preventive medications (MPMs). More extensive polysomnography (PSG)-based studies for this purpose were not available. Objective To investigate possible sleep changes in patients with migraine treated with erenumab, using validated sleep questionnaires and home-PSG. Methods This observational, prospective, open-label pilot study was conducted at the Clinical Neurology Unit Headache Center of Udine University Hospital from 2020 to 2021. Patients were treated with erenumab as monotherapy or add-on treatment for migraine prevention. Sleep changes were evaluated with questionnaires and polysomnographic recordings at baseline, after 3 and 12 months of treatment. Erenumab efficacy and safety in migraine prophylaxis were also investigated. Results Twenty-nine patients completed 3 months of follow-up, whereas 15 patients completed 12 months. We found a weak trend of improvement in daytime somnolence after 3 months of treatment, with stronger results after 12 months (median Epworth Sleepiness Scale (ESS) score from 6.0 to 4.0, p = 0.015); a significant improvement in subjective sleep quality (median Pittsburgh Sleep Quality Index (PSQI) total score from 7 to 5; p = 0.001) was also observed. Home-PSG showed a significant increase in objective sleep efficiency (SE), both after 3 (from 88.1 to 91.0, p = 0.006) and 12 months (from 87.1 to 91.0, p = 0.006) of treatment. In addition, our data confirmed erenumab effectiveness and safety in migraine prevention. Conclusion Our study demonstrated an improvement in both subjective and objective sleep quality in patients treated with a migraine-preventive therapy. Erenumab, in particular, does not cross the blood-brain barrier (BBB), thus a direct effect on sleep is unlikely. Future studies are needed to better understand the mutual influence between migraine and sleep disorders.